Pengaruh Pengetahuan Dewan Tentang Anggaran Terhadap Fungsi Pengawasan APBD Pada DPR Kabupaten Lebong - Aswar, Aswar; Astuty, Kamelia; Effendi, Bahman (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2024)
The Regional Budget is essentially a policy instrument used as a tool to improve public services and community welfare in the region. DPRD and local governments must make real and structured efforts to produce APBDs that can reflect the real needs of the community in accordance with the potential of each region, and can meet the demands of creating a regional budget that is oriented towards the interests of the community. This research is quantitative descriptive research, which is a study that serves to describe or provide an overview of the object under study through sample or population data with numbers using data that the author thinks is in accordance with the object of research and provides an overview of the object of research.Knowledge of the council on the budget has a positive and significant effect on the role of members of the Lebong Regency DPRD, Bengkulu in supervising regional finances. This is because based on the test results on respondents' answers, it shows the results that members of the Lebong Regency DPRD, Bengkulu have good or high knowledge about the budget. In the reliability test results show the results of reliability testing on variable X instruments with a Cronbach's Alpha value of 0.624. The results of the reliability test on variable Y instrument with a Cronbach's Alpha value of 0.627. This proves that the research instrument in the form of a questionnaire is reliable because Cronbach's Alpha is greater than 0.60. In the validity test results, it can be seen that the correlation between each indicator of variables X and Y shows significant results and shows that R count> R table (0.320). It can be concluded that all question items are declared valid.